Structural performance of 1 way and 2 way setback with the soft first story using ddbd - Anis Rosyidah; Indriyana Luthfiyanti (Jurnal Teknosains, 2022)
Irregular building structures increasingly varied, such as setback buildings and buildings with soft level stiffness irregularity on the first floor of the building (soft first story). High-rise buildings are at risk of collapse due to earthquakes. Designing efficiency requires a Direct Displacement Based Design (DDBD) method. In this study, the DDBD method uses pushover analysis on soft first-story buildings without a setback,1-way setback, and 2-way setback. This study aims to obtain the value software's value of displacement, story drift, ductility, plastic hinge response, and performance levels study indicates that the displacement value of the soft first-story building without setback is smaller than the setback building. In addition, the value of displacement and story drift in the setback building with a soft first story is influenced by the small setback area ratio. The highest displacement and story drift values in the X direction are 1-way setback buildings, which are 0.422 m and 0.0147 m, while in the Y-direction, the 2-way setback buildings are 0.44 m and 0.0167 m. The most significant value of actual ductility is a building without setbacks with a soft first-story. The plastic hinge response in all three buildings shows a strong column weak beam. The level of structural performance in all three buildings is at the level of Immediate Occupancy, where the value of the performance level of the FEMA 356 method is greater than the ATC 40 method.